﻿Formulação de novos combustíveis base diesel: avaliação de desempenho e emissões - Fernandes, Manoel Reginaldo (2011)
The industry, over the years, has been working to improve the efficiency of diesel engines. More recently, it was observed the need to reduce pollutant emissions to conform to the stringent environmental regulations. This has attached a great interest to develop researches in order to replace the petroleum-based fuels by several types of less polluting fuels, such as blends of diesel oil with vegetable oil esters and diesel fuel with vegetable oils and alcohol, emulsions, and also microemulsions. The main objective of this work was the development of microemulsion systems using nonionic surfactants that belong to the Nonylphenols ethoxylated group and Lauric ethoxylated alcohol group, ethanol/diesel blends, and diesel/biodiesel blends for use in diesel engines. First, in order to select the microemulsion systems, ternary phase diagrams of the used blends were obtained. The systems were composed by: nonionic surfactants, water as polar phase, and diesel fuel or diesel/biodiesel blends as apolar phase. The microemulsion systems and blends, which represent the studied fuels, were characterized by density, viscosity, cetane number and flash point. It was also evaluated the effect of temperature in the stability of microemulsion systems, the performance of the engine, and the emissions of carbon monoxide, nitrogen oxides, unburned hydrocarbons, and smoke for all studied blends. Tests of specific fuel consumption as a function of engine power were accomplished in a cycle diesel engine on a dynamometer bench and the emissions were evaluated using a GreenLine 8000 analyzer. The obtained results showed a slight increase in fuel consumption when microemulsion systems and diesel/biodiesel blends were burned, but it was observed a reduction in the emission of nitrogen oxides, unburned hydrocarbons, smoke index and f sulfur oxides